Inferior Vena Cava Thrombosis in a Patient with Factor V Leiden Syndrome Presenting with Scrotal Pain - Helmy Elhag; Fadl Al-Tairy; Mohammed Shakeeb Dahdaha; Ahmed Shaeshaa; Yavuz Yigit (Case Reports in Medicine)
Thrombosis in the inferior vena cava (IVC) is a rare but serious condition that can lead to significant morbidity and mortality. We present a case report of a 39-year-old male who presented to the emergency department with right flank pain that had progressed to severe back pain, bilateral flank pain, scrotal pain, and leg pain over the course of two days. The pain was severe enough to affect his daily activities. Laboratory investigations revealed a D-dimer level of 17 ng/mL, creatinine level of 110 µmol/L, and a white blood cell count of 10 × 109/L with a CRP level of 5 mg/L. Urine analysis was positive for blood. Doppler ultrasound of both legs showed deep vein thrombosis extending from the external iliac veins to the distal veins of both legs. Further investigation with computed tomography of the abdomen revealed a large thrombus in the distal vena cava extending to the renal artery and both external and internal iliac veins. The patient was diagnosed with Factor V Leiden syndrome based on genetic testing, which revealed a heterozygous mutation in the F5 gene. He was successfully treated with low molecular weight heparin and warfarin, and after five days of hospitalization, he was discharged with warfarin for long-term anticoagulation. This case report emphasizes the importance of considering IVC thrombosis in patients with a constellation of symptoms, including scrotal pain, and the role of genetic testing in identifying underlying hypercoagulable states.